The Impact of The Implementation of The Latest Auditing Standards on The Quality of Financial Statements - Pasaribu, Lamtiur; Situmorang, Riadul Zannah; Nazwa, Syafira (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This study aims to analyze the impact of the implementation of the latest auditing standards on the quality of financial statements. The latest auditing standards refer to the guidelines and procedures applied by auditors in conducting audits of an entity's financial statements. This research applies a qualitative research approach in our writing. The method of analysis we apply is a literature study that analyzes the content of articles from online-based sources, such as Google Scholar. We collected and processed this data from journal abstracts that included information about the author, year of journal publication, a brief description of the research, research objectives, samples used, and measurement results or findings found in the article. From the results of these studies, it can be concluded that the implementation of the latest auditing standards has a positive impact on the quality of financial statements. Factors such as audit quality, auditor independence, auditor experience, and audit structure also play an important role in shaping the quality of financial statements. Therefore, auditors and public accounting firms need to maintain independence, improve audit quality, and keep abreast of the latest audit standards to ensure optimal financial statement quality